“Lambe-Lambe” theater: a theater of possibilities (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The present paper, part of a doctoral thesis in progress at the Graduate Program in Culture and Society at the Federal University of Bahia (Pós-Cultura/UFBA), seeks to examine a type of theater known as “lambe-lambe,” utilizing the basic concepts that guide the actors that created it, puppet artists Ismine Lima (1950-2022) and Denise di Santos. The paper also explores this type of theater’s pedagogical and emancipatory potential, based on the artistic practice developed by students at the Center for Culture, Expressions and Applied Technologies of the Federal University of the Bahian Recôncavo (Cecult/UFRB).
Keywords: Lambe-Lambe Theater; Animated Theater; UFRB